Faktor-Faktor Yang Mempengaruhi Penyaluran Kredit - Rahmatullah, Suci; Iryani, Nelvia (Universitas Gorontalo, 2023)
This study's goal was to examine the variables Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), and Return on Assets (ROA) that have an impact on lending at PT BPR Suliki Gunung Mas (ROA). Time series data are the type of secondary data that was used for the investigation. Analysis is conducted using multiple linear regression. According to the study's findings, lending is significantly impacted by the variables NPL, LDR, and ROA at the same time. Over the period of 2013–2022, the LDR variable at PT BPR Suliki Gunung Mas has a positive and negligible influence on lending, but the NPL and ROA variables have a somewhat negative and substantial impact.